Intrinsic pinning by naturally occurring correlated defects in FeSe1-xTex superconductors - Amigó, M.L.; Ale Crivillero, M.V.; Franco, D.G.; Badía-Majós, A.; Guimpel, J.; Campo, J.; Damay, F.; Porcher, F.; Condó, A.M.; Nieva, G.; Guimpel, Julio; Amigó, María Lourdes; et al. (IOP Publishing, 2017)
Fil: Amigó, M.L. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina; Universidad Nacional de Cuyo; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina